Sosialisasi Gerakan “Mas AL” dalam Pelayanan Publik Saat Pandemi Covid-19 di Kelurahan Bintoro, Demak - Marthalina Marthalina; Dwi Ayu Sulistyaningrum (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2021)
The Covid-19 pandemic attracted writers to conduct community service activities in the form of socialization of the “MAS AL” movement aimed at preventing the transmission of Covid-19 in the service process in Bintoro Subdistrict Demak. The movement “MAS AL” is an abbreviation that means Applying 4M; Apply healthy living; Always praying; Always smile &happy. The “MAS AL” movement is an effort to raise awareness in the prevention of Covid-19 which is packaged by the author in the form of an interesting and memorable slogan. This study uses qualitative descriptive research method as a problem solving procedure while the method of community service implementation is a step or way that the author in finding solutions to problems encountered by the author in the Binotoro Village Government in organizing service activities to the community during the Covid-19 pandemic. Community service activities that have been carried out by the author there is a conclusion (1) socialization related to the prevention of Covid-19 has been running in an orderly and smooth manner both direct socialization and socialization through social media (2) socialization movement “MAS AL” get high appreciation from Camar Demak and Lurah Bintoro and all village and community apparatus, (3) village officials and community residents who have not previously been disciplined to start te rtib and discipline in complying with health protocols as stipulated by the government, (4) Poster Movement “MAS AL” used by Lurah Bintoro in bintoro office as a reminder of the discipline of health protocols and clean and healthy lifestyle for village officials and citizens (5) is encouraged there needs to be further research on social media usage behavior especially if it is associated with pandemic conditions Covid-19.